The Influence of Entrepreneurial Orientation, Entrepreneurial Competence, and Market Orientation on Business Performance of Batik MSMEs in Magelang Regency - Belva, Dicky Bramanta; Kurnia, Marlina (Innovation, Technology, and Entrepreneurship Journal, 2025)
This study aims to analyze the effect of entrepreneurial orientation, entrepreneurial competence, and market orientation on the business performance of Batik MSMEs in Magelang Regency. The research method used is quantitative with a multiple linear regression approach. Data were obtained through a survey of 100 Batik MSME entrepreneurs in Magelang Regency. The results showed that entrepreneurial orientation has a positive and significant effect on business performance. Entrepreneurial competence also has a positive and significant effect, indicating that increased entrepreneurial skills and knowledge can enhance business sustainability. Additionally, market orientation was found to have a positive and significant effect, suggesting that understanding consumer needs and market trends is crucial for increasing the competitiveness of MSMEs. The implication of this research is the need for increased entrepreneurship training and market-oriented marketing strategies to support the growth of Batik MSMEs in Magelang Regency.